1961
DOI: 10.1107/s0365110x61002163
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of pentacene

Abstract: Crystals of pentacene are triclinic, with two molecules in a unit cell of dimensions a = 7.93, b = 6" 14, c= 16.03 A, a= 101.9 °, fl= 112.6 °, y =85.8 °, space group Pi. The structure, which has been determined from projections along the a and b crystal axes, is very similar to the structures of naphthalene, anthracene and tetracene. The two molecules in the unit cell are situated on independent centres of symmetry, the asymmetric unit consisting of two half-molecules. Both molecules are completely planar. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
258
3
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 344 publications
(294 citation statements)
references
References 0 publications
27
258
3
5
Order By: Relevance
“…The pentacene-HT unit cell is consistent with the unit cell first reported by Campbell et al [5] The crystal structure of pentacene-HT is shown in Figure 1, with the low-temperature polymorph (pentacene-LT) superimposed to illustrate the relative molecular displacements. Individual herringbone-type layers are virtually identical and can be superimposed on each other, whereas adjacent layers are shifted in the pentacene-LT crystal system by (0.295, -0.174, 0.033) in fractional coordinates, or by (1.74 Å, -1.23 Å, 0.47 Å) in an orthogonal system with the x-axis parallel to the a-axis, and the z-axis parallel to the c*-axis.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…The pentacene-HT unit cell is consistent with the unit cell first reported by Campbell et al [5] The crystal structure of pentacene-HT is shown in Figure 1, with the low-temperature polymorph (pentacene-LT) superimposed to illustrate the relative molecular displacements. Individual herringbone-type layers are virtually identical and can be superimposed on each other, whereas adjacent layers are shifted in the pentacene-LT crystal system by (0.295, -0.174, 0.033) in fractional coordinates, or by (1.74 Å, -1.23 Å, 0.47 Å) in an orthogonal system with the x-axis parallel to the a-axis, and the z-axis parallel to the c*-axis.…”
supporting
confidence: 85%
“…A recent attempt to reproduce the solution growth of pentacene from trichlorobenzene used a temperature of 450 K to slowly evaporate the solvent. [9] This yielded pentacene-LT, because the growth temperature was below the transformation temperature of 463 K. However, if the crystal growth described by Campbell [5] was carried out at a temperature above 463 K, but below the boiling point of trichlorobenzene of 486 K, pentacene-HT would be more stable, and fast cooling may have allowed pentacene-HT to be quenched to room temperature.…”
Section: Unit-cell Parametersmentioning
confidence: 99%
See 3 more Smart Citations